The Anti-Cruelty Society - Stanley Tigerman (Oz, 1982)
The program called for a second generation addition to a 1933 building designed in "Chicago World's Fair Moderne" with a 1953 appendage done in International Style Modern.'' The existing complex's intrinsic architectural message was hermetically institutional...